MOTOR ASSESSMENT IN PRESCHOOL CHILDREN: A COMPARATIVE STUDY (Fiep Bulletin - online, 2011)
The aim of this study was to evaluate the psychomotor diagnose motor age of pre - school children, and to examine whether regional customs influence the development of the same engine. Participants 138 children of both sexes aged from 4.6 to 6.10 years, 117 were enrolled in the School Urbana located in Manaus, AM, 57 of those were during the mornings (they had no physical education classes) and 60 the morning hours (they had two classes per week of physical education). The other 21 subjects were from the Rural School, located in the Village of Lindenow / Itacoatiara. The instrument was the Scale of Motor Development. The tests were Kinetics Global (Gk), Fine Motor (FM), Equilibrium (EQ), Bory schema  (BS), Spatial Orientation (SO) and Temporal Orientation (TO). We performed semi-structured interviews with parents of the subjects to check the activities that they perform at the time of leisure. The results obtained were analyzed by IM in each event and discussed by the descriptive analysis, mean and standard deviation between the CI and MI obtained as performance on tests. We used ANOVA (normal distribution) and Krusskal Wallis (non-normal distribution) to determine differences between groups, significance level p
Keywords: motor development; motor age; motor ability